2020
DOI: 10.1039/d0ta00871k
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilizing hydrophilic and hydrophobic polymers via spray coating for desalination

Abstract: The incompatibility between PVA and PTFE layers was overcome by spray-coating and the PVA/PTFE composite membrane showed excellent desalination properties in both PV and DCMD experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Compared with solutionbased membrane modification such as spray-coating, [13a,18] this vapor-based modification did not involve wetting or dewetting, thus no need to overcome the large surface energy difference between the hydrophilic and hydrophobic components. [16][17][18] The asymmetric deposition of P(MAA-co-EGDA) and PHDFA was confirmed using FTIR spectroscopy. As shown in Figure 2, the absorption peaks at 1735, 1201, and 1147 cm −1 are assigned to the stretching of CO, CF 3 , and CF 2 functional groups in PHDFA, respectively.…”
Section: Fabrication and Characterization Of Janus Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with solutionbased membrane modification such as spray-coating, [13a,18] this vapor-based modification did not involve wetting or dewetting, thus no need to overcome the large surface energy difference between the hydrophilic and hydrophobic components. [16][17][18] The asymmetric deposition of P(MAA-co-EGDA) and PHDFA was confirmed using FTIR spectroscopy. As shown in Figure 2, the absorption peaks at 1735, 1201, and 1147 cm −1 are assigned to the stretching of CO, CF 3 , and CF 2 functional groups in PHDFA, respectively.…”
Section: Fabrication and Characterization Of Janus Membranesmentioning
confidence: 99%
“…[11][12][13][14] In addition, the conflicting wettability of hydrophilic and hydrophobic components made the solvent-based methods less effective and resulted in poor interfacial compatibility. [18] To facilitate the attaching of hydrophilic coatings onto the liquid-repelling hydrophobic structure, protocols such as plasma activation, [16] chemical modification, [19] Janus membranes with excellent fouling resistance and mass transport properties are highly desired to improve the performance and efficiency in the treatment of oil-contaminated wastewater. The fabrication of Janus membranes requires control of both the membrane microstructure and the interfacial compatibility between distinct components.…”
mentioning
confidence: 99%
“…Over the last two decades, membrane-based separation technologies have attracted a great deal of attention because they have merits such as high energy efficiency, low capital investment, 1 environmentally friendly, simple operation, and small footprint. [2][3][4] However, in harsh operational conditions such as natural gas purification 5 or recovery of landfill gas, conventional polymeric membranes may undergo physical aging or plasticization that deteriorates the gas separation property. 1,6 Therefore, it is necessary to develop membranes having a better stability in extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, through the force balance analysis, the thin air film via the dimple affects the droplet's bouncing regardless of the surface's wettability. Furthermore, in industrial technologies such as a solution-based process, e.g., printing or spray coating, the air film caused by the dimple can reduce the mechanical adhesion of the deposited layer or be an obstacle such as a pinhole defect to hinder electrical/chemical performance of the device [20][21][22]. To sum up, irrespective of the field that the droplet coalescence happens, the air film (dimple) becomes a significant factor that cannot be ignorable in droplet coalescence.…”
Section: Introductionmentioning
confidence: 99%